2019
DOI: 10.1111/cge.13499
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional mosaicism in RASA1‐related capillary malformation‐arteriovenous malformation

Abstract: Capillary malformation‐arteriovenous malformation (CM‐AVM) is caused by germline RASA1 and EPHB4 alterations. RASA1 intralesional second hits have also been reported. Here we report RASA1 constitutional mosaicism, defined here as the presence of a mosaic variant in all cell types of an individual, in two patients with CM‐AVM. High‐throughput sequencing was used to search for RASA1 pathogenic variants in blood samples from two unrelated patients with CM‐AVM. An affected tissue sample from one of the patients wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…As de novo mutation rate is estimated to be as high as 25%,3 4 it was logical to also identify mosaic mutations, like in other autosomal dominant disorders with high de novo mutation rate, such as in tuberous sclerosis 8. While our manuscript was under review, another group published RASA1 mosaic mutations in two patients with CM-AVM 9. Our study reinforces these results.…”
Section: Discussionsupporting
confidence: 82%
“…As de novo mutation rate is estimated to be as high as 25%,3 4 it was logical to also identify mosaic mutations, like in other autosomal dominant disorders with high de novo mutation rate, such as in tuberous sclerosis 8. While our manuscript was under review, another group published RASA1 mosaic mutations in two patients with CM-AVM 9. Our study reinforces these results.…”
Section: Discussionsupporting
confidence: 82%
“…Also, three patients with GNAQ: p.Arg183Gln variants presented with KTS/DCMO. Furthermore, protein truncating variants in RASA1 , reported in Parkes Weber syndrome,46 50–53 were found in three patients (germline or somatic) with a phenotype partially overlapping KTS/DCMO, two of which without typical arteriovenous malformations. In this respect, it seems relevant to point out that the cases we studied have been accumulated over 10 years, a time period in which some clinical definitions have changed, such as that between KTS and DCMO, and this might have impacted on our clinical classification 40…”
Section: Discussionmentioning
confidence: 98%
“…The intrafamilial variability and the multifocal lesions in PKWS involving segmental overgrowth of soft tissue, endothelium, and bone are strongly suggestive of a somatic second-hit model (Lapinski et al 2018). To date, there are at least two case reports of confirmed second somatic hits in RASA1 (one germline and one somatic) (Revencu et al 2013;Macmurdo et al 2016;Gordo et al 2019)-only one of them with proven somatic second hit in trans of the germline pathogenic change (Lapinski et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Given recent reports in the literature and collective clinical experience, there is increasing evidence to support that a substantial number of patients with segmental overgrowth syndromes (with or without vascular dysplasias) are caused by somatic pathogenic variants without necessarily having germline involvement (Gordo et al 2018(Gordo et al , 2019. A recent publication by Gordo et al (2019) reported two unrelated occurrences of CM-AVM caused by constitutional RASA1 pathogenic mosaic variants detected in a blood sample and the affected tissue in one of the affected individuals. There was no evidence of a second hit identified in the affected tissue.…”
Section: Discussionmentioning
confidence: 99%